The Influence of Capital Structure and Credit Risk On Profitability in Companies Banks Listed on the Stock Exchange Indonesia (BEI) Period (2019-2023) - Debby Debora Violeta Mauk; Junita C. Nenabu; Lustry Rahayu (Entrepreneurship Faculty, Universitas Garut, 2026)
The findings indicate that it is effective management of funding composition and credit quality is crucial for maintaining banking stability and enhancing financial performance. Simultaneously, capital structure (DER) and credit risk (NPL) exert a significant influence on profitability (ROA), accounting for 43.7% of its variations. Partially, capital structure (DER) shows a negative and significant impact on ROA, US higher debt proportions increase interest burdens and financial risk, thereby suppressing profitability. In contrast, credit risk (NPL) demonstrates a positive but insignificant effect on ROA, reflecting that NPL fluctuations remain within manageable levels and can be mitigated through operational efficiency and revenue diversification. This quantitative study employed a causal approach, analyzing data panel using regression techniques with selection-based model on the Chow and Hausman tests. The population comprised 47 banking listed firms on the IDX during 2019–2023, with 20 firms selected through purposive sampling. This study was conducted to examine the influence of capital structure and credit risk on bank profitability.